The induced decomposition of t-butyl peroxide in solution. Part II. Kinetic study - Goh, S.H.; Ong, S.H. (Royal Society of Chemistry, 1970)
The rate of decomposition of t-butyl peroxide in ρ-chloro-, m-chloro-, and 3,4-dichloro-benzyl methyl ether was found to be reduced in the presence of α-methylstyrene, confirming the occurrence of SH2 attack on t-butyl peroxide by the ether radical. The decomposition of the peroxide in 3,4-dichlorobenzyl methyl ether was of the first order in peroxide, indicating that dimerisation of the ether radical and t-butoxyl radical constituted the main termination step in the chain decomposition of t-butyl peroxide. Data on the relative rate of decomposition of t-butyl peroxide in a variety of solvents indicate that induced decomposition occurs in aromatic and halogenated compounds in addition to ether.